Methods for adjusting feedback in terahertz lasers - Dzyubenko, M.I.; Maslov, V.A.; Radionov, V.P.; Fomin, A.A. (Radiotekhnika, 2020)
The optimal feedback coefficient in an active open resonator is an important condition for high lasing efficiency. For precise selection of the optimum communication and maintaining the optimum in all modes of laser operation, the ability to adjust smoothly the communication is required. Terahertz (THz) lasers have a number of features that one should take into account when choosing feedback control schemes. The paper presents a review and comparative analysis of the schemes of laser resonators (THz) in the range with a smoothly controlled radiation output. The authors consider both long known and widely used, as well as the latest schemes of laser resonators. Smooth adjustment can be realized in resonators formed by metal mirrors of total internal reflection and output mirrors in the form of metal mirrors with holes or one-dimensional metal gratings. The analysis of the advantages and disadvantages of each of the considered optical schemes of laser resonators is carried out. It is shown that the given resonator schemes make it possible to control and optimize the feedback in the laser during its operation. All of them are not very complex and can be realized by re-equipping existing lasers. The choice of a specific scheme should be made in accordance with the specifics of the laser application. The use of resonators with smooth coupling control makes it possible to achieve high efficiency of lasers at all energy operating modes.